Regulation of Fixed-Term Employment Agreements on Working Time and Part-Time Wages in Labor Law - Narendra Khairafi Cahyandi; Aidul Fitriciada Azhari (Universitas Muhammadiyah Surakarta, 2025)
This research was prepared with the aim of providing information related to working time and wages, as well as legal protection for part-time workers based on labor law. This research is studied using a qualitative research method using a juridical-normative approach. The juridical-normative approach in this research is carried out by tracing legal documents and laws and regulations related to the title discussed by the researcher. The results of this research show that the Government of the Republic of Indonesia provides legal protection for part-time workers so that employers cannot be arbitrary in terms of division of working time and work wages for part-time workers.